DIURETIC RADIONUCLIDE RENOGRAPHY IN ASSESSING ANDERSON-HYNES PYELOPLASTY IN UNILATERAL PELVI-URETERIC JUNCTION OBSTRUCTION - Khan, Mazhar; Khan, Wasim Yar; Ahmad, Riaz; Ghani, Fazal (Journal of Postgraduate Medical Institute, 2011)
Objective: To analyze the functional outcome of unilateral Anderson Hynes (AH) Pyeloplasty using DTPA renography in patients with symptomatic pelvi- ureteric junction (PUJ) obstruction. Material and Methods: This study included 48 patients with PUJ-obstruction who underwent stentless AH pyeloplasty. Their record was analyzed for age, clinical presentation, pre and postoperative IVU and preoperative and postoperative DTPA renography finding. The out come of the pyeloplasty was evaluated by comparing preoperative and postoperative symptomatic improvement and DTPA renography split function result. Results: The age range from 3yrs 25yrs with mean age 19.68 yrs. The were 35 (72.9%) male and 13(27.1%) female. The left side was involved in 31(64.58%), right side in 10(20.83%) and 7 (14.58%) patients had bilateral PUJ -obstruction. The predominant clinical presentation was pain in 36(75%), urinary tract infection in 4(8.33%), haematuria in 2(4.16%), while in 8(16.66%) patients it was an incidental finding. The patients were divided into 3 groups based on the renography split function. Group A: 20-30% function, 16 (33.33%) patients; Group B: 31-40% function, 12(25%) patients and Group C: >40% function, 20 (41.66%) patients. Post pyeloplasty scan revealed stable renal function in 19(39.58%) patients, while improvement was noticed in 21(43.75%) patients. The remaining 8(16.66%) had deterioration in renal function. Conclusion: Anderson-Hynes Pyeloplasty is an effective treatment for PUJ-obstruction. 99mT-DTPA renal scan is an important investigation in diagnosing PUJ-obstruction and evaluating the outcome of surgical intervention.